2015
DOI: 10.1080/13102818.2015.1008228
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis of a medicinal fungiPhellinus linteusand identification of SSR markers

Abstract: The aim of this study was to facilitate gene discovery for functional genome studies and to identify simple sequence repeat (SSR) markers for molecular-assisted selection in Phellinus linteus. The transcriptome of Phellinus linteus was sequenced using а high-throughput RNA sequencing system – the Illumina Hiseq 2000. A total of 16,383,818 clean sequencing reads, 35,532 contigs and 25,811 unigenes were postulated. Based on similarity searches with known proteins, 19,350 genes (74.97% of the unigenes) were annot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In addition, 38 EST-SSRs were present in compound formations ( Figure 1 ). The finding of TNR as the most abundant repeat motif in the Bailinggu transcriptome is similar to studies of many other fungi, such as A. polytricha [ 29 ], Lentinula edodes [ 30 ], Boletus edulis [ 31 ], Volvariella volvacea [ 32 ] and Phellinus linteus [ 14 ]. Therefore, a high frequency of tri-nucleotide repeats might be a common feature in EST-derived SSRs.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, 38 EST-SSRs were present in compound formations ( Figure 1 ). The finding of TNR as the most abundant repeat motif in the Bailinggu transcriptome is similar to studies of many other fungi, such as A. polytricha [ 29 ], Lentinula edodes [ 30 ], Boletus edulis [ 31 ], Volvariella volvacea [ 32 ] and Phellinus linteus [ 14 ]. Therefore, a high frequency of tri-nucleotide repeats might be a common feature in EST-derived SSRs.…”
Section: Resultssupporting
confidence: 80%
“…Transcriptome sequencing is an efficient, cost-effective way to develop expressed sequence tag-simple sequence repeat (EST-SSR) markers. EST-SSR markers have been useful for the assessment of genetic diversity surveys, construction of genetic maps, cultivar identification and other related studies [ 5 , 13 , 14 , 15 , 16 ]. However, research related to the use of molecular markers for identifying monokaryons and their corresponding genetic diversity, mating types and hybrid offspring in Bailinggu breeding is limited [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the maping rate only reached 61–73%, which indicated that there are great variation in gene content between this strain and G. lucidum . The de novo assembled transcriptome of G. oregonense SLZ72 revealed that the GC content of G. oregonense unigenes was approximately 58.08%, which was higher than in the genomes of Phellinus linteus (51.49%) 32 , Amanita exitialis (51.58%) 33 , Lentinula edodes (48.3%) 34 , Pleurotus ostreatus genome (50.9%) 35 , G. lucidum G.260125-1 (56.10%) 36 , G. lucidum Xiangnong No.1 (55.30%) 37 , and G. lucidum BCRC 37177 (55.50%) 38 . However, its GC content was lower than Auricularia polytricha (61.3%) 39 .…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, a newly developed platform (Illumina Hiseq 2000/2500) has been successfully used in de novo sequencing experiments, providing a new transcriptome sequencing approach for non-model species, especially fungal species, without a reference genome (Zhang et al, 2013a ; Liu et al, 2014 ; Lou et al, 2014 ). This platform can produce a large amount of genetic information for many analysis types, such as comparative transcriptome analysis (Quan et al, 2015 ; Qiu et al, 2016 ), SSR identification (Yu et al, 2014 ; Huang et al, 2015 ) and uncovering unknown biosynthesis/metabolism pathways, in particular (Zhang et al, 2015 ; Zondag et al, 2016 ). Compared with the 454 technology and other sequencing platforms, the Illumina platform has optimized the traditional sequencing method, and is advantageous in its high throughput, high sensitivity, high accuracy and low cost, distinguishing it from its competitors.…”
Section: Introductionmentioning
confidence: 99%